Pengaruh Kualitas Pelayanan Terhadap Loyalitas Konsumen Gofood Melalui Kepuasan Konsumen - Rusminah HS; Hilmiati Hilmiati; H.M. Ilhamudin (Universitas Mataram, 2023)
The research aims to analyze whether service quality affects GoFood consumer loyalty through consumer satisfaction. This type of research is associative quantitative research, which is used to find out the effect of service quality on GoFood consumer loyalty through consumer satisfaction. The population in this study is the people of the city of Mataram who use the GoFood service feature on the Gojek application, with a sample of 100 respondents. Sampling technique with Non-Probability sampling technique with purposive sampling method. Data collection techniques used questionnaires and documentation. While the data collection tool used is a questionnaire that is uploaded on the Googleform website and provides a link to the respondent. The data analysis used is Structural Equation Modeling (SEM) analysis using the Partial Least Square (PLS) program. Mandatory and additional outputs are articles in accredited national journals and policy recommendations. The results of the study show that service quality has a positive and significant effect on consumer loyalty in the GoFood application, customer satisfaction has a positive and significant effect on consumer loyalty in the GoFood application and service quality has a positive and significant effect on customer satisfaction in the GoFood application.